2015
DOI: 10.1007/s40616-015-0043-1
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Verbal Behavior: a Status Update

Abstract: We analyzed past volumes of The Analysis of Verbal Behavior (TAVB) to provide a comprehensive status update after 30 years of publication. Data on TAVB's content, frequent contributors, and scholarly impact suggest a healthy state of the journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…In particular, there was a large increase in citations from empirical articles, including basic and experimental analyses that appeared to be directly influenced by Skinner (1957) in that one or more independent or dependent variables were conceptualized as verbal operants. These results are encouraging for the experimental analysis of verbal behavior and corroborate previous reports of increased empirical research activity related to verbal behavior in the past decade (Aguirre et al, 2016;Luke & Carr, 2015). A citation analysis, however, may not capture all such activity.…”
Section: Applied Experimental Analysissupporting
confidence: 82%
See 1 more Smart Citation
“…In particular, there was a large increase in citations from empirical articles, including basic and experimental analyses that appeared to be directly influenced by Skinner (1957) in that one or more independent or dependent variables were conceptualized as verbal operants. These results are encouraging for the experimental analysis of verbal behavior and corroborate previous reports of increased empirical research activity related to verbal behavior in the past decade (Aguirre et al, 2016;Luke & Carr, 2015). A citation analysis, however, may not capture all such activity.…”
Section: Applied Experimental Analysissupporting
confidence: 82%
“…However, there is evidence that during this time, there has been a substantial further increase in empirical research activity influenced by Skinner's (1957) analysis. A sharp increase in the number of empirical articles published each year in The Analysis of Verbal Behavior (TAVB) during this period has already been documented (Luke & Carr, 2015;Marcon-Dawson, Vicars, & Miguel, 2009;Presti & Moderato, 2016), and a recent article (Aguirre, Valentino, & LeBlanc, 2016) reported a large increase in empirical research on intraverbal behavior (data on other verbal operant classes were not reported). The purpose of the present study is to provide a more comprehensive analysis of the influence of Verbal Behavior on the scholarly literature from 2005 through 2016.…”
mentioning
confidence: 99%
“…Several bibliometric analyses of TAVB articles have surveyed aspects of the journal, such as characteristics of published articles (Luke & Carr, 2015;Marcon-Dawson, Vicars, and Miguel, 2009;Normand, Fossa, and Poling, 2000), citation patterns (Critchfield, Buskist, and Saville, 2000;Luke & Carr), and TAVB's impact on other journals (Luke & Carr, 2015). Results from prior reviews suggest that TAVB is maturing with respect to its content and scholarly impact.…”
mentioning
confidence: 99%
“…Results from prior reviews suggest that TAVB is maturing with respect to its content and scholarly impact. Publication analyses found an increasing number of empirical articles that adhered to the methodological standards of the experimental analysis of behavior and included a broad range of research in recent years, extending beyond basic verbal relations to address such topics as autoclitics (Luke & Carr, 2015;Marcon-Dawson et al, 2009;Normand et al, 2008). Citation analyses reveal that classical sources (e.g., Skinner, 1957) and recent empirical research are cited in TAVB empirical articles (Critchfield et al).…”
mentioning
confidence: 99%
See 1 more Smart Citation